Acute Circulatory Collapse Followed by Cardiac Arrest during Thiopentone Induction - Ali, Md Rashid; Rahman, Md Jobaidur; Khan, Kamrul Russel; Adam, Shamim; Alam, Shamsul (KYAMC Journal, 2017)
Acute circulatory collapse followed by cardiac arrest is a rare but serious complication of thiopentone anaesthesia. A 5 years old boy admitted in North Bengal Medical College Hospital with history of 'Recurrent Tonsillitis'. He was prepared for tonsillectomy operation. The reports of his clinical investigations were almost normal except E.S.R which was a bit elevated-09%. X-Ray chest was normal, other investigatios did not show any abnormalities. During induction with Thiopentone Sodium the patient had sudden cardiac arrest. In spite of all life support given to him the patient did not recover. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 731-733